KEUNGGULAN POTENSI DESA MENUMBUHKAN EKONOMI MASYARAKAT DI DESA MATARU TIMUR KECAMATAN MATARU - Senti Atakari; Silas Maniata; Petrus Mau Tellu Dony; Imanuel Y.H. Manapa (Adiba Aisha Amira, 2026)
This study aims to examine the advantages of village potential in growing the communty’s economy in Mataru Timur Village,Mataru District,Alor Regency. Mataru timur village has quite large and diverse natural resource potential,especially in the agricultural and plantation sectors. Superior commodities such as candlenut,porang,and vanilla are strategic assets in driving the economic growth of the village community’s economy through the utilization of local resources. The method used is a qualitative descriptive approach with data collection techniques,observation,interviews,and documentation of village officals. The result of the study indicate that optimal management of potential can increase community income. In addition,the utilization of local potentialn also encourages economic independence and strengthens village economic resilience. However,support is still needed in the from of increasing human resource capacity,market access,and related parties so that village government and related parties so that existing potential can be developed sustainably. With proper management,the potential of mataru timur village can become a driving force in improving community welfare.